Purification of Antibodies From Human Milk and Infant Digestates for Viral Inhibition Assays - Sah, Baidya Nath P.; Lueangsakulthai, Jiraporn; Hauser, Benjamin R.; Demers-Mathieu, Veronique; Scottoline, Brian; Pastey, Manoj K.; Dallas, David C. (Frontiers in Nutrition, 2020)
Oral administration of enteric pathogen-specific immunoglobulins may be an ideal approach for preventing infectious diarrhea in infants and children. For oral administration to be effective, antibodies must survive functionally intact within the highly proteolytic digestive tract. As an initial step toward assessing the viability of this approach, we examined the survival of palivizumab, a recombinant monoclonal antibody (IgG1κ), across infant digestion and its ability to neutralize respiratory syncytial virus (RSV). Human milk and infant digestive samples contain substances known to interfere with the RSV neutralization assay (our selected functional test for antibody survival through digestion), therefore, antibody extraction from the matrix was required prior to performing the assay. The efficacy of various approaches for palivizumab purification from human milk, infant's gastric and intestinal digestates, including casein precipitation, salting out, molecular weight cut-off, and affinity chromatography (protein A and G) were compared. Affinity chromatography using protein G with high-salt elution followed by 30-kDa molecular weight cut-off centrifugal filtration was the most effective technique for purifying palivizumab from human milk and infant digestates with a high yield and reduced background interference for the viral neutralization assay. This work is broadly applicable to the optimal isolation of antibodies from human milk and infant digesta for viral neutralization assays, enables the examination of how digestion affects the viral neutralization capacity of antibodies within milk and digestive samples, and paves the way for assessment of the viability of oral administration of recombinant antibodies as a therapeutic approach to prevent enteric pathogen-induced infectious diarrhea in infants.